Program Aplikasi Pengelolaan Kas Menggunakan Php Pada Klinik Dyna Banjarmasin - Muhammad Syahid Pebriadi; Ahsanul Haq; Fuji Melania (Universitas Sains dan Teknologi Komputer, 2021)
Clinic is a health service institution that is used to provide medical services needed by the community. The clinic aims to help improve the quality of health in the community and the clinic can be managed by the government or the private sector. In order to create good and fast service to the community, it can be supported by computerized accounting records. The purpose of this study is to determine the appropriate cash management accounting information system at DYNA Clinic in Banjarmasin, as well as to produce a Web-Based Cash Management Application Program This study found that all cash records at the DYNA clinic were still manual. The author suggests using a web-based cash management application program to help DYNA Clinic record patient data, record cash management transactions and make it easier to find information on cash receipts and disbursements.